The Great Resignation: Understanding the Reasons Behind the Mass Exodus of Employees and Finding Solutions - Hidayat, Muhammad; Ihsan, Adi Muhammad Nur (Management Studies and Business Journal (PRODUCTIVITY), 2024)
The Great Resignation phenomenon, characterized by a significant increase in employee resignation rates, has become a global concern following the COVID-19 pandemic. This research aims to understand the impact of generational differences on the reasons and consequences of this phenomenon. The research method used is a systematic literature review using databases such as Scopus and Web of Science. The results showed that factors such as work-life balance, job satisfaction, and organizational commitment vary among different generations. The implications of these findings emphasize the importance of organizations in developing retention strategies that suit generational characteristics to reduce turnover rates and increase employee satisfaction. This research also highlights the need for more attention to employee mental health and wellbeing as part of an effective retention strategy.